The Role of the Young Generation in Forming Character and Morals Pan-casila: A Case Study of Patriarchy in Bugul Lor Village, Pasuruan City - Mumtaza, Yasmin; Mujiwati, Yuniar; Alisa, Zahra Nur; Rizki, Amalia Putri (Jurnal Ilmu Pendidikan dan Humaniora, 2025)
Although many feminist groups and women activists are fighting for women's rights, patriarchal cultural practices are still deeply rooted, especially in Indonesia. This culture views women as inferior beings who must submit to men, resulting in gender discrimination and restrictions on women's roles in various aspects of life. This article discusses the Role of the Young Generation in Shaping Pancasila Character and Morals against Patriarchy Cases in Bugul Lor Village, Pasuruan City. This research focuses on the views of the younger generation with several informants chosen by the researcher, 5 women and 2 men in the age range between 19 to 27 years old, in Bugul Lor Village, Pasuruan. The method used is descriptive qualitative, with data collection through observation, documentation, and interviews with young people. The results of this study are the perceptions of the younger generation in Kelurahan Bugul Lor, which show that patriarchy still dominates, with rigid gender roles and unfair division of tasks. Young people realize that patriarchy is an unfair system and has the potential to hinder social progress and women's welfare. To overcome patriarchy, the younger generation needs to change existing social and cultural norms and raise awareness of gender equality. Pancasila can be used as a foundation to build fairer morals and character. This research contributes to the development of science by offering new insights into the challenges of changing patriarchal social structures and recommending more effective strategies to empower women and promote gender equality in society. The practical implications of this research can also serve as a reference for educators and policy makers in formulating programs that support gender equality and the strengthening of Pancasila values among the younger generation